Being white is a full time job? Explaining skin tone gradients in income in Mexico. Issue 1 (2nd January 2021) - Reeskens, Tim; Velasco Aguilar, Rodrigo
ABSTRACT: While scholarship on wage discrimination has confirmed that 'racism' is persistent, recent insights indicate that 'colorism' – the idea that lighter skin tones are rewarded more compared to darker ones, all else equal – is often more relevant in some societies where race or ethnicity are less salient markers. In this article, the following underlying theoretical mechanisms are discussed and are subjected to an empirical test: differential investment in human capital, i.e. education; variation in occupational status, i.e. being employed in indoor white-collar vs outdoor blue-collar jobs; and concentration in richer vs poorer regions. Mexico, known as a country where race and ethnicity generally are less salient categories for social stratification while skin tone is more important, is used as a case. Based on regression analyses on the most recent 2017 wave of the National Survey on Discrimination in Mexico, we show that there is an effect of skin tone on income that is explained by differences in education, occupational status and, to a lesser extent, regional concentration. Triangulating the findings with data from 2010 indicate that if colorism is at work, it are the lightest tones that are privileged, not the darkest ones that are penalised.